Geriatrics for Specialists - Burton, John R.; Lee, Andrew G.; Potter, Jane F. (Springer International Publishing : Imprint: Springer, 2017)
This book focuses on the circumstances that lead to the marked increased vulnerability of seniors and are most challenging to clinicians including the presence of multiple chronic medical conditions, variable losses of physiological function, and heterogeneity among individuals. Written by the experts who lead the initiative to deliver high quality surgical and medical care to the elderly, Geriatrics for Specialists is the first book of its kind to provide the comprehensive knowledge specialists and associated generalists need to deliver quality health care to seniors. With topics on important cross cutting issues like frailty, delirium and polypharmacy and specialty chapters on emergency medicine, anesthesia, many surgical and medical disciplines and rehabilitation, this book provides clinicians the knowledge and tools needed to evaluate, treat and manage the unique needs of seniors. Geriatrics for Specialists was created as a resource for specialist, generalists and allied health professionals and their students and trainees who care for elderly patients.
Keywords: Medicine.; General practice (Medicine).; Critical care medicine.; Geriatrics.; Nursing.; Primary care (Medicine).; elektronické knihy; electronic books